Penyembuhan Islam dan Otoritas Keagamaan: Studi Kasus Ustaz Dhanu - Mupida, Siti (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2020)
The phenomenon of the settlement of Islam and religious authority is significant to studied, becouse it is the concept of forming a new religious authority in the contemporary. This paper begins to explain the concept of authority as seen from the process of commodification and religification. As well as the thought of the restoration of the religious teacher Dhanu recoveri as a purification of Islamic recovery. To answer this question, the authors conducted field observation and discussed literature, as well as conducted several empirical studies on various alternative treatments offline and online. Data obtained though participant observation and documentation, as well as literature studies. After the data is collected, data analysis is carried out though the process of analyzing data, classifying, reducing data, interpreting data, and making conclusions. The results of this study are the rehabilitation of Islam created by the Dhanu cleric which can be seen through television and youtube sites and shows, making history of the recovery of Islam, culture, and political economy. The salient difference from Dhanu’s recovery is the claim of purificative healing and criticism of the use of magic and spells by shamans or clerics. This healing of Dhanu give birth to a new religious authority in the Islamic world.